Rhegmatogenous retinal detachment: current treatment approaches - A.V. Doga; D.O. Shkvorchenko; L.A. Kryl; M.R. Taevere; D.A. Buryakov (РМЖ "Клиническая офтальмология")
A.V. Doga, D.O. Shkvorchenko, L.A. Kryl’, M.R. Taevere, D.A. Buryakov S.N. Fedorov NMRC “MNTK “Eye Microsurgery”, Moscow, Russian Federation Rhegmatogenous retinal detachment (RRD) is a severe eye disease that may result in low vision or blindness in the lack of surgery. Three major surgical techniques for RRD are currently available, i.e., scleral buckling, pars plana vitrectomy, and pneumatic retinopexy. These techniques are successfully used for RRD as their primary efficacy is up to 90%. However, pneumatic retinopexy and scleral buckling do not completely eliminate vitreomacular tractions. In addition, these techniques can induce refractive errors, i.e., astigmatism and myopia. Meanwhile, vitrectomy may result in postoperative complications (i.e., cataract, secondary ocular hypertension, emulsification of silicone oil, keratopathy, and suprachoroidal hemorrhage). Therefore, there is disagreement regarding preferences for surgery. This paper discusses routine and promising surgical techniques for RRD, compare these techniques, and reviews novel technologies and randomized clinical studies that will sign ificantly improve surgical outcomes. Keywords: rhegmatogenous retinal detachment, scleral buckling, vitrectomy, pneumatic retinopexy, YAG-laser retinotomy. For citation: Doga A.V., Shkvorchenko D.O., Kryl’ L.A. et al. Rhegmatogenous retinal detachment: current treatment approaches. Russian Journal of Clinical Ophthalmology. 2020;20(2):72–78. DOI: 10.32364/2311-7729-2020-20-2-72-78.